2001
DOI: 10.1515/cclm.2001.158
|View full text |Cite
|
Sign up to set email alerts
|

Reference Intervals from Birth to Adulthood for Serum Thyroxine (T4), Triiodothyronine (T3), free T3, free T4, Thyroxine Binding Globulin (TBG) and Thyrotropin (TSH)

Abstract: Disorders in thyroid function can impair normal development in children. Therefore it was our aim to establish reference intervals for serum triiodothyronine (T3), free T3 (fT3), thyroxine (T4), free T4 (fT4), thyroxine binding globulin (TBG) and thyrotropin (TSH) which are applicable from birth to adulthood by using the non-isotopic automated chemiluminescence immunoassay system, Immulite (DPC Los Angeles, USA). Serum samples from 762 euthyroid newborns, children and adolescents (369 female, 393 male; age 1 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
94
2
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(115 citation statements)
references
References 6 publications
11
94
2
6
Order By: Relevance
“…Our findings for LH, FSH, TT3, and FT3 agree with earlier studies on the Abbott IMx [11]. The data of Elmlinger utilized n values varying from 8 to 131 in the various age groups with many groups having an n<30 [12,13]. Despite this deficiency the data are similar to those in this manuscript which utilizes n values falling between n=45 and n=289.…”
Section: Resultssupporting
confidence: 88%
“…Our findings for LH, FSH, TT3, and FT3 agree with earlier studies on the Abbott IMx [11]. The data of Elmlinger utilized n values varying from 8 to 131 in the various age groups with many groups having an n<30 [12,13]. Despite this deficiency the data are similar to those in this manuscript which utilizes n values falling between n=45 and n=289.…”
Section: Resultssupporting
confidence: 88%
“…The FT 4 increase and TSH decrease developed gradually, after day 3 but before day 15 in neonates who subsequently developed hyperthyroidism. (Table 1) are consistent with the previously described time-course of FT 4 , FT 3 , and TSH values in neonates, once gestational age at birth is taken into account (25,36,37). When interpreting thyroid function data in neonates, the values must be compared with age-specific normal ranges.…”
Section: /Atdsupporting
confidence: 86%
“…An intensive inpatient two-month weight-loss program for children and adolescents indicated that the change in TSH with weight loss predicted reductions in HOMA-IR after controlling for change in body weight, age, and sex, while the changes in fT3 and fT4 did not (37). Sex-related differences were observed in TSH, fT3 levels, and the fT3:fT4 ratios in this NHANES adolescent cohort, but since data on sexual maturity rating (Tanner Staging) were not recorded, it was not possible to assess the impact of pubertal progression on thyroid hormone levels directly, for which studies are conflicting (38,39). The variability in these results highlights the need for further prospective studies elucidating the relations between thyroid hormones, TSH, and weight fluctuations in children and adolescents at various stages of pubertal development.…”
Section: Discussionmentioning
confidence: 84%